Leyes y reglamentos de Instrucción pública vigentes : compilados y concordados de orden del congreso de 1890. - Cáceres, Rafael (1892)
Leyes y reglamentos de Instrucción pública vigentes : compilados y concordados de orden del congreso de 1890.